Brilliant cresyl blue staining negatively affects mitochondrial functions in porcine oocytes. Issue 3 (June 2015) - Santos, E.C.S.; Sato, D.; Lucia, T.; Iwata, H.
Summary The aim of the present study was to examine the effects of brilliant cresyl blue (BCB) staining on mitochondrial functions in porcine oocytes. Cumulus–oocyte complexes (COCs) collected from slaughterhouse-derived porcine ovaries were cultured with (13 μM) or without (0 μM, control) BCB for 60 min. Mitochondrial functions in oocytes were examined immediately after staining or after in vitro maturation. The BCB-stained oocytes produced reactive oxygen species (ROS) at higher levels than control oocytes immediately after staining (2.2-fold, P < 0.001) and after maturation (1.7-fold, P < 0.001). The adenosine triphosphate (ATP) content and mitochondrial membrane potential (MMP) in oocytes were similar for the two groups immediately after staining. However, ATP and relative MMP levels were significantly (P < 0.05) lower in BCB-treated oocytes than in the control (2.18 versus 2.83 pM and 0.82 versus 1.0, respectively). There was no difference in mitochondrial DNA copy number between the two groups after maturation. The ATP content in early developmental stage embryos (3 days after parthenogenetic activation) was lower in the BCB-stained group than that in the control group but the difference was not significant. In conclusion, BCB staining of oocytes at the immature stage compromises mitochondrial functions throughout oocyte maturation, but function is restored during early embryo development.